Deskripsi Tingkat Kecemasan Perawat Saat Bertugas di Ruang Perawatan Covid-19: Description of the Anxiety Level of Nurses While on Duty in the COVID-19 Care Ward. - Yarwin Yari; Teti Oktianingsih; Irma gita; Desi Luanda; M.Khalid Fredy; Wawan Kurniawan; Neneng Ilah Rohilah; Idawati; Deny Alfiansyah; Ida Farida (MPI Press, 2021)
Introduction: Novel Coronavirus Disease (Covid-19) caused by SARS-COV2 was first discovered in Wuhan, China, December 2019. WHO has designated Covid 19 as a pandemic which has resulted in an increase in mortality worldwide. Covid-19 attacks the respiratory system similar to pneumonia but has signs of decreased oxygen saturation. In Indonesia, all health workers and paramedics, especially for a nurse, must always be ready to serve and provide direct care, the transmission rate is very high and the number of cases is increasing every day. This will make nurses as health workers have more workloads and are very vulnerable to experiencing psychological problems in the form of anxiety. Objectives: This study aims to describe the anxiety level of nurses working in the COVID-19 isolation room. Method: This type of research is an analytic study with a cross sectional design. Total population 100 people, with inclusion and exclusion criteria. Result: This study showed that most of the nurses did not experience anxiety, 97 respondents (77.6%), 16 respondents (12.8%) mild anxiety, 11 respondents (8.8%), moderate anxiety, and 1 respondent (0.8%) severe anxiety. Conclusion: the picture of anxiety in nurses who work in the Covid-19 isolation room has the ability to respond to anxiety well.